PEMANFAATAN LIMBAH SERABUT (FIBER) KELAPA SAWIT DALAM PEMBUATAN POT ORGANIK - Jaka Darma Jaya; Adzani Ghani Ilmannafian; Maimunah Maimunah (Teknik Lingkungan Universitas Islam Indonesia, 2019)
Plastic pots are widely used in agriculture and forestry nurseries. Its popular use has resulted in the increased pollution to the environment because they can not be decomposed by soil microorganism. It is therefore necessary to find an alternative substitute for pots made from an organic material. This study was aimed to optimize the composition of the addition of natural adhesives in the manufacture of organic pots made from fiber as palm oil waste. Furthermore, this research was conducted to characterize the physical and level of acceptance of organic pots. This study used an experimental method where results are concluded from the water content, water absorption, hedonic test and hedonic quality test. The organic pot moisture content was between 10.11-10.59%, while the absorption of organic pot water was between 129.25-155.48%. Pot with the lowest moisture content and water absorption was obtained from P2 treatment. The result of hedonic test shown that the highest level of pot acceptance in terms of color was the pot of treatment P5 and the texture aspect was the pot of treatment P1. Keywords: fiber, gambier, organic pots, tapioca